2012
DOI: 10.3171/2012.9.jns121227
|View full text |Cite
|
Sign up to set email alerts
|

Impaired pulsation absorber mechanism in idiopathic normal pressure hydrocephalus

Abstract: The results suggest that the human intracranial system shows frequency dependence as seen in animal experiments. There is an inverse relationship between CPA index and ICP amplitude, indicating that higher amplitudes may occur with a reduced performance of the pulsation absorber. Our findings show that frequency dependence can be observed in humans and imply that reduced frequency-dependent compliance may be responsible for elevated ICP amplitude observed in patients who respond to CSF shunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The physiological role of the astrocytic endfeet is debated, but it may be proposed that the volume regulation of the endfeet may act as a pulsation absorber for the arterial blood pressure pulsations created by cardiac contractions. In previous studies, we proposed the existence of a cardiac pulsation absorbance from a biophysical and pressure signaling perspective [28], but without an underlying biological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological role of the astrocytic endfeet is debated, but it may be proposed that the volume regulation of the endfeet may act as a pulsation absorber for the arterial blood pressure pulsations created by cardiac contractions. In previous studies, we proposed the existence of a cardiac pulsation absorbance from a biophysical and pressure signaling perspective [28], but without an underlying biological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Previous canine studies have demonstrated that brain compliance is dynamic and displays a frequency‐dependent function with enhanced pulsatility absorbance around cardiac frequency . This phenomenon is diminished in canine models of hydrocephalus as well as in INPH patients . In keeping with these experimental findings, Eide and Sorteberg demonstrated that 93% of patients with increased ICP pulsatility improved after shunt surgery compared with only 10% of patients without increased ICP pulsatility.…”
Section: Pathophysiologymentioning
confidence: 66%
“…Animal and hydrodynamic human studies have implicated elevations of CSF pressure as a core defect in INPH . The increased frequency of episodic pressure elevations, called B‐waves, observed on continuous intracranial pressure (ICP) monitoring is consistent with this . It is generally accepted that this increased ICP pulse amplitude suggests a decrease in brain compliance, which may play a central role in INPH pathophysiology .…”
Section: Pathophysiologymentioning
confidence: 79%
“…20 Impaired intracranial compliance and elevated ICP wave amplitudes can also be associated with reduced function of intracranial absorber mechanisms. 36 Prior to shunting of hydrocephalus, the ICP wave amplitudes in patients are elevated, indicative of impaired intracranial compliance. 22 Moreover, shunting normalizes the ICP waves, and adjustment of opening pressure can tailor levels of ICP waves.…”
Section: Icp Scores and Type Of Shunt Failurementioning
confidence: 99%